Polar patrol balloon project in Antarctica - Nagata, Takesi; Fukunishi, Hiroshi; Nishimura, Jun; Kodama, Masahiro; Co-Members of PPB Working Group (1985)
P(論文) We are planning to carry out a circumpolar ballooning project called "Polar Patrol Balloon (PPB)" project. The main objective of the PPB project is to establish a station network at altitudes higher than 30km over the Antarctic for the studies of upper atmosphere physics, cosmic ray physics, meteorology and glaciology. Feasibility studies of the project and the development of new technology for long-duration flight have been commenced in April 1984 by the PPB working group organized in the National Institute of Polar Research. By using zero-pressure balloons with an auto-ballasting system, it is expected that PPB launched from a station in Antarctica will land near the launching site about three weeks later with meridional deviation less than about ±2°in the case of a midsummer 30km-level flight. This paper gives an outline of this project. departmental bulletin paper